Kidney injury molecule-1; is it a predictive marker for renal diseases? - Deepashree Goravigere Anandkumar; Prashant Chippalkatti Dheerendra; Deepesh Vellakampadi; Gnanasambandan Ramanathan (Society of Diabetic Nephropathy Prevention, 2023)
Kidney injury is the main cause of mortality and morbidity globally. The kidney injury molecule (KIM-1) is a type 1 transmembrane protein, which is been upregulated during renal injury at high levels in urine, serum, plasma, and tissues and plays a crucial role in the pathogenesis of renal diseases. Kidney injury molecule has been used as a marker for the diagnosis of renal disease at an early stage as well as to predict the progression of disease with a clinical outcome. This review article aims to discuss and summarize the available literature data regarding KIM-1 being a potential marker for diagnostic, therapeutic, and prognosis of clinical outcomes and management in kidney diseases. We also discuss the relationship between KIM-1 and kidney injury in a few common renal diseases such as acute pyelonephritis, acute tubular nephrosis (ATN), diabetic kidney disease (DKD), acute kidney injury (AKI), chronic kidney disease (CKD), and other pathologies.